Post-Quantization and Glitch in the Music of Nicole Lizée. Nicole Lizée in Conversation with Ben Duinker - Duinker, Ben (Revue musicale OICRM, 2025)
Award-winning composer and video artist Nicole Lizée creates new music inspired by an eclectic mix of influences including the earliest MTV videos, turntablism, rave culture, Hitchcock, Kubrick, Alexander McQueen, thrash metal, early video game culture, 1960s psychedelia, and 1960s modernism. She is fascinated by the glitches made by outmoded and well-worn technology and captures these glitches, notates them and integrates them into live performance.As a percussionist and chamber musician, I’ve had the pleasure of commissioning, touring and recording Lizée’s music, as well as performing it alongside her. Often synced to films created by the composer herself, Lizée’s compositions require devoted and sustained engagement from performers. This engagement rewards musicians and audiences alike by facilitating a deeper connection with the music––its crafting of the experience of time and stewardship of adrenaline and energy. Lizée gave a keynote address at the second Rhythm in 20th Century Music Conference at McGill University, her alma mater, in September 2023. This interview reflects and elaborates on that talk.